Sundanese Dining Etiquette as a Medium for Character and Moral Development in Children: Parental Contributions - Septiawati, Chindy Suji; Mirawati; Asriadi AM, Muh; Halimah, Leli (Indonesian Values and Character Education Journal, 2024)
The lack of attention to instilling proper etiquette in daily life can affect the development of children’s character and moral intelligence. Sundanese dining etiquette, as a cultural heritage, serves as a medium to instill moral values and build the character of younger generations. This study aims to analyze the role of parents in instilling Sundanese dining etiquette to achieve children's moral intelligence. The research method employed is a Systematic Literature Review (SLR) by conducting a literature search on electronic databases, including Google Scholar, ERIC, and Taylor and Francis. A total of 30 relevant articles were thematically analyzed and presented in tables and narrative analysis. The findings reveal that parents play a crucial role as educators, role models, and supervisors in supporting children to achieve moral intelligence. The stages children experience include moral knowing, moral feeling, and moral action. The habituation of Sundanese dining etiquette, through strong collaboration between mothers and fathers, positively impacts children’s character formation, such as independence, discipline, and politeness. This study concludes that parents' active roles in guiding and supervising their children during each stage of moral development are essential for achieving moral intelligence. Expanding the scope of literature is recommended to explore other local cultures as alternatives for fostering children’s moral intelligence.